Screening of Potential Compounds in Tomato (Solanum lycopersicum) as Candidates for Anti Diabetes Mellitus Complications - Narwasthu, Sekararum; Fahmi, Muhamad; Kurnianingsih, Nia; Wihastuti, Titin Andri; Fatchiyah, Fatchiyah (Universitas Gadjah Mada, 2024)
This study aimed to identify the potential of natural compounds in tomatoes for diabetic complications intervention using amino acid profile, HP-TLC, antioxidant assay, enzymatic inhibitor assay, and in silico approach. Fresh air-dried tomatoes were analyzed for several screening assays including amino acid determination, HP-TLC, antioxidant activity using FRAP, α-amylase, and α-glucosidase enzyme inhibition. Virtual screening, molecular docking and molecular dynamics were performed using Molinspiration, pKcSM, AutoDock Vina, Discovery Studio, PyMOL, and Yasara software. Tomato bioactive compounds showed promising drug-likeness, antioxidant and α-amylase/glucosidase inhibitory activities, and potential for AGE-RAGE interaction. Out of 19 compounds from whole tomatoes complying with Lipinski’s rule of five, genistein, apigenin, and naringenin exhibited high oral absorption potential. Tomato contains genistein compound based on HP-TLC and the compound has high antioxidant and antidiabetic activities. Genistein has a stronger binding affinity with RAGE compared to AGE, indicating its potential as a competitive inhibitor. Additionally, genistein displayed stable ligand movements and higher binding energy values in MD simulations compared to the control. These findings suggest the potential of tomato bioactive compounds for further development as antidiabetic agents targeting AGE-RAGE interaction. In conclusion, genistein in tomatoes is indicated as a candidate for anti-complications of diabetes mellitus.